UJI EFEKTIVITAS EKSTRAK CIPLUKAN (PHYSALLIS ANGULATA) TERHADAP PENURUNAN KADAR GLUKOSA DARAH PADA TIKUS JANTAN GALUR WISTAR - Liska Marlinda Sari; Haty Latifah Priatni; Azmi Darotulmutmainnah (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2023)
Ciplukan chemical compounds containing flavonoids. Flavonoid act as antioxidants. The ability of flavonoids as antioxidants can reduce oxidative stress and reduce ROS (Reactive Oxygen Species). This can lead to a protective effect on beta cells of the pancreas and increases insulin sensitivity. This study aims to determine the effectiveness and on how many levels extract ciplukan (Physallis angulata) which has effectivenes on reducing blood glucose in male rats induced by alloxan. This test uses an experimental method. Statistical data processing using one-way ANOVA and t-tes. This test is performed on 18 rats were divided into 6 group negative control which was given distilled water solution, positive control group treated with a solution of metformin, the normal group was not given any treatment, and the 3 group was given the extract solution ciplukan with a dose 3mg, 6mg, dan 9mg. The results showed the existence of differences in each extract treatment provision ciplukan. Of the 3 variants dose ciplukan extract the most effective in lowering blood glucose levels in male rats that 3mg dose, but by doing so the effect can not be equated with the positive control.